2021
DOI: 10.1124/jpet.121.000537
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase Inhibitors for Arsenic Trioxide–Resistant Acute Promyelocytic Leukemia: Synergistic In Vitro Antitumor Effects with Hypomethylating Agents or High-Dose Vitamin C

Abstract: Arsenic trioxide (ATO) is an anticancer agent used for the treatment of acute promyelocytic leukemia (APL). However, 5-10% of patients fail to respond or experience disease relapse. Based on poly(ADP-ribose) polymerase 1 (PARP1) involvement in the processing of DNA demethylation, here we have tested the in vitro susceptibility of ATO-resistant clones, derived from the human APL cell line NB4, to PARP inhibitors (PARPi) in combination with hypomethylating agents (azacitidine and decitabine) or high-dose vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…Similar results on the efficacy of PARPi and hypomethylating agents were also demonstrated in AML and breast cancer [90,91]. Furthermore, different types of PARPi showed promising therapeutic effects for treating arsenic trioxide-acute promyelocytic leukaemia (APL) in combination with DNMTi or high-dose ascorbate that is shown to increase 5hmC and thus the DNA demethylating ability of TET enzymes [92].…”
Section: Epigenetic Mechanisms In Parpi-based Cancer Therapymentioning
confidence: 53%
“…Similar results on the efficacy of PARPi and hypomethylating agents were also demonstrated in AML and breast cancer [90,91]. Furthermore, different types of PARPi showed promising therapeutic effects for treating arsenic trioxide-acute promyelocytic leukaemia (APL) in combination with DNMTi or high-dose ascorbate that is shown to increase 5hmC and thus the DNA demethylating ability of TET enzymes [92].…”
Section: Epigenetic Mechanisms In Parpi-based Cancer Therapymentioning
confidence: 53%
“…Particularly, PARP14 can promote glycolysis in different tumor models, such as human hepatocellular carcinoma (HCC), by maintaining reduced PKM2 activity (Iansante et al, 2015); on the other hand, a close relationship between c-myc and AKT has been reported in B lymphomas (Cho et al, 2011) and AML through the NF-κB/HIF-1α axis (Zhu et al, 2022). Interestingly, the use of Niraparib, a PARP1/2 inhibitor, decreases resistance to ATO and hypomethylating agents (azacytidine and decitabine) in tumor promyelocytes (Giansanti et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Few studies are available on the efficacy of niraparib in acute leukemias. Niraparib, as well as other PARPs inhibitors, was effective against arsenic trioxide (ATO)-resistant acute promyelocytic leukemia (APL) primary cells alone and in combination with hypomethylating agents (azacitidine and decitabine) or high-dose vitamin C (ascorbate) [ 111 ]. The synergism was dependent on the role of PARP1 protein in the processing of DNA demethylation.…”
Section: Preclinical Data Of Currently Available Parp Inhibitors In A...mentioning
confidence: 99%